Integrated Framework for Secure and Energy Efficient Communication System in Heterogeneous Sensory Application - Yogeesh AC; Shantakumar B. Patil; Premjyoti Patil; Roopashree HR (Institute of Advanced Engineering and Science, 2019)
Irrespective of different forms and strategies implementing for securing Wireless Sensor Network (WSN), there are very less strategies that offers cost effective security over heterogeneous network. Therefore, this paper presents an integrated set of different processes that emphasize over secure routing, intellectual and delay-compensated routing, and optimization principle with a sole intention of securing the communication to and from the sensor nodes during data aggregation. The processed system advocates the non-usage of complex cryptography and encourages the usage of probability their and analytical modelling in order to render more practical implementation. The simulated outcome of study shows that proposed system offers reduced delay, more throughputs, and reduced energy consumption in contrast to existing system.